Fasting improves blood lipid profile - Khattak, Muhammad Muzaffar Ali Khan; Abu Bakar, Ibrahim; Yiem, L. (2009)
Fasting is performed in different communities with different believes and for the management of body weight but in Islam the Muslim observes fasting in the Holy Month of Ramadan as an obligation. Therefore, this study was designed to know the effect of fasting on the body weight and blood lipids. Twenty five volunteers (male & female) from the international Islamic University Malaysia (IIUM) were recruited in Ramadan. Weight, height and blood samples were collected on the Day1 of the Ramadan and followed by another three collection .i.e. day7, 14 & 21. The body weight was also recorded on day 21. The blood serum was separated and stored at -20C̊. From weight & height basal metabolic Index (BMI) was determined. The blood was analyzed for glucose and lipid profiles by Bayer Health Care Kits. The BMI was reduced by1.88 percent on the day 21 of Ramadan. There was a decreasing trend in blood glucose concentration from day 1-21 and the decrease was 10.00%. The blood triglyceride concentration significantly reduced and the reduction was 17.48 percent from day 1-21. The blood total-Cholesterol concentration also reduced from day 1-21 and the reduction was 15.93 percent. The blood LDL-Cholesterol concentration also significantly reduced from day 1-21 and the reduction was 21.67 percent. The blood HDL-Cholesterol concentration decreased in the first weak and second week but improving trend 21 was observed on day 21 of the Ramadan. This study indicates that Islamic fasting could be a useful tool for the management of body weight and blood lipids.